Comparison of the Sexual Function among Women with and without Diabetes - Azam Parnan; Mahin Tafazolim; Elham Azmoude (Journal of Midwifery & Reproductive Health, 2017)
Background & aim: Globally, diabetes is one of the most common chronic diseases, which is considered as the leading cause of sexual dysfunction. However, its effect on female sexual function is still inconspicuous. This study aimed to compare diabetic and non-diabetic women in terms of sexual function. Methods: This cross-sectional study was conducted on 180 diabetic and non-diabetic (n=90 for each group) women referring to the health facilities of Mashhad, Iran. The subjects were married, aged between 18 to 60 years and had experienced type II diabetes for at least one year. Data were collected using clinical and demographic characteristics questionnaire and Rosen’s Female Sexual Functioning Index. To analyse the data, analysis of covariance (ANCOVA), independent t-test, Mann-Whitney U test, and Chi-square test were run using SPSS, version 16. Results: The mean age of diabetic and non-diabetic was respectively 52.42±9.8 and 43.58±9.39. ANCOVA reflected a significant difference between diabetic and non-diabetic women in terms of total score of sexual function (P=0.002) and the score of five domains of desire (P=0.004), arousal (0.001), lubrication (0.003), orgasm (0.001) and satisfaction (0.002). Conclusion: Diabetes is a risk factor for sexual dysfunction in women, which causes negative effects on their sexual function; therefore, it is recommended to educate patients to protect them against these adverse effects.